A Neglected Issue in Ulcerative Colitis: Mesenteric Lymph Nodes - Sahin, Abdurrahman; Artas, Hakan; Eroglu, Yesim; Tunc, Nurettin; Oguz, Gulcan; Demirel, Ulvi; Bahcecioglu, Ibrahim Halil (Mdpi, 2018)
Data evaluating the presence and characteristics of mesenteric lymph nodes (LNs) in patients with ulcerative colitis (UC) are scarce. The aim of this study is to determine the presence and characteristics of LNs in UC. The LN characteristics in computed tomography (CT), including LN dimension and attenuation, were evaluated retrospectively in 100 patients with UC (61 active and 39 inactive cases). Clinical characteristics and laboratory parameters, including CBC, biochemical analysis, erythrocyte sedimentation rate (ESR), and C reactive protein (CRP) were also compared. Mesenteric LNs were evident in all patients with UC. The attenuation and dimension of mesenteric LNs did not differ between active and inactive patients with UC. No correlation was found among patients with UC in terms of LN dimension, attenuation, ESR, CRP, leucocyte, and albumin (all with p > 0.05). The current study suggested that inflammation results in the development of mesenteric LN in UC, similar to Crohn's disease and other inflammatory disorders.
Keywords: ulcerative colitis; mesenteric lymph node; attenuation; dimension